MORPHOLOGICAL CHARACTERISTICS OF THE ANTERIOR WALL CELL COMPLEX OF THE FRONTAL RECESS AND ITS ASSOCIATION WITH FRONTAL SINUS OPACIFICATION ON CT SCAN (Vietnam Journal of Community Medicine, 2026)
Objectives: To describe the morphology and prevalence of the frontal recess anterior wall cellular complex and evaluate its association with frontal sinus opacification on CT scan.Methods: A cross-sectional study was conducted on 174 patients at Nhan Dan Gia Dinh Hospital from January 2024 to June 2025. Anterior wall structures were identified on multiplanar CT and compared with frontal sinus opacification according to Lund-Mackay scores. Generalized Estimating Equations (GEE) were used to account for within-subject correlation between the two sides.Results: Agger nasi cells were present in 90.6% of sides. Frontal cells (Kuhn classification) were observed in 45.6%. Agger nasi cells were associated with higher rates of frontal sinus opacification (OR=3.45; 95% CI: 1.18–10.12; p=0.035). The rate of opacification tended to increase with anatomical complexity: 12.5% in sides without Agger nasi or frontal cells, 22.8% in sides with isolated Agger nasi cells, and 32.9% in sides with both Agger nasi and frontal cells (p=0.032). High - extension frontal cells (Kuhn type III and IV) showed a trend towards higher opacification rates (48.5%) compared to low - extension types (28.7%), although this did not reach statistical significance (p=0.052).Conclusion: The anterior wall cellular complex is an anatomical factor associated with frontal sinus opacification on CT scan. The coexistence of Agger nasi and frontal cells may suggest a combined narrowing effect within the frontal recess.
Keywords: Anterior wall complex, Agger nasi cell, frontal cell, frontal recess, frontal sinus opacification